Femoral artery anatomy-tailored approach in transcatheter aortic valve implantation - Olasinska-Wisniewska, Anna; Grygier, Marek; Lesiak, Maciej; Araszkiewicz, Aleksander; Trojnarska, Olga; Komosa, Anna; Misterski, Marcin; Jemielity, Marek; Proch, Marek; Grajek, Stefan (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction : The best techniques for reduction of femoral access site complications after transcatheter aortic valve implantation (TAVI) remain the object of research. Aim : We report on a single center’s experience with TAVI performed via the femoral access site. Material and methods : Between September 2010 and September 2015, 152 consecutive patients underwent TAVI in our department. Of them, 101 patients with CoreValve implantation from the femoral access site were included in the analysis. The femoral artery anatomy-tailored approach was introduced in 2013 in order to reduce the rate of access-site complications. Patients were assigned to percutaneous puncture or surgical cut-down depending on the femoral artery anatomy assessed in computed tomography. The study patients were divided into two subgroups: group A – patients treated before January 2013, before introduction of the tailored approach program (n = 34); and group B – patients treated between January 2013 and April 2015 (n = 67). Results : The access site complication rate significantly decreased from 35.3% in group A (n = 12) to 7.5% in group B (n = 5) (p = 0.0012). Both minor and major access site complications were more frequent in group A (p = 0.04 and 0.016, respectively). In-hospital mortality was 8.8% (n = 3) in group A and 1.5% (n = 1) in group B (p = 0.1). Conclusions : The femoral artery anatomy-tailored approach significantly reduces the incidence of access site complications in TAVI patients.